2006
DOI: 10.2174/157488506775268515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Cyclophosphamide and Ifosfamide

Abstract: The oxazaphosphorine cyclophosphamide (CPA) and ifosfamide (IFO) are two commonly used DNAalkylating agents in cancer chemotherapy. This review highlights the pharmacokinetics and pharmacodynamics of the two important agents. As alkylating agents, CPA and IFO are usually combined with other anticancer drugs in the chemotherapy of solid tumors and hematological malignancies to obtain synergistic or additive anticancer effect due to complementary mechanism of action. Both compounds are prodrugs that are activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 380 publications
(463 reference statements)
2
85
0
1
Order By: Relevance
“…CP is one of the most effective chemotherapeutic agents used in the treatment of cancers of breast (Levine et al, 2005;Hirano et al, 2008), lung (Sundstrom et al, 2005;Zhang et al, 2006), prostate (Nicolini et al, 2004), ovary (Donato et al, 2004), leukemia (Rao et al, 2005), lymphomas and non-Hodgkin's lymphoma. Significantly different from the CP-treated group using one-way ANOVA followed by the Tukey-Kramer multiple comparisons test (p50.05).…”
Section: Discussionmentioning
confidence: 99%
“…CP is one of the most effective chemotherapeutic agents used in the treatment of cancers of breast (Levine et al, 2005;Hirano et al, 2008), lung (Sundstrom et al, 2005;Zhang et al, 2006), prostate (Nicolini et al, 2004), ovary (Donato et al, 2004), leukemia (Rao et al, 2005), lymphomas and non-Hodgkin's lymphoma. Significantly different from the CP-treated group using one-way ANOVA followed by the Tukey-Kramer multiple comparisons test (p50.05).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggested that CP generates active metabolites, like 4-hydroxycyclophosphamide, phosphoramide mustard and acrolein. These metabolites preferably alkylate N 7 position of the guanine residue of DNA and this leads to inter-and intra-strand cross-links, DNA strand breaks, cessation of DNA synthesis, DNA-protein cross-links and DNA adduct formation (15). There are a lot of studies on genotoxicity of CP.…”
Section: Discussionmentioning
confidence: 99%
“…CP is activated by hepatic cytochrome P450 (CYP) isoenzymes, to form 4-hydroxycyclophosphamide, which enters the blood and is transported to tumor cells by erythrocytes. 1 Because CP is activated by CYP-catalyzed metabolites, drug interactions could modulate the pharmacokinetics by inhibition of a relevant CYP. 1 Hesperidin has been shown to significantly affect the pharmacokinetics of several drugs, such as diltiazem and verapamil, by inhibition of CYP isoenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because CP is activated by CYP-catalyzed metabolites, drug interactions could modulate the pharmacokinetics by inhibition of a relevant CYP. 1 Hesperidin has been shown to significantly affect the pharmacokinetics of several drugs, such as diltiazem and verapamil, by inhibition of CYP isoenzymes. 12-15 P-glycoprotein 1 (permeability glycoprotein, abbreviated as P-gp or Pgp) also known as multidrugresistant protein 1 is a glycoprotein that in humans has several families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation